Challenges regarding integration and well-being of African Ukrainian war refugees in Germany: a qualitative exploration - Adedeji, Adekunle; Kaltenbach, Stella; Buchcik, Johanna; Fagbemigun, Taiwo; Hanft-Robert, Saskia (Frontiers in Human Dynamics, 2025)
The study explores the integration challenges of African refugees who fled the war in Ukraine and sought asylum in Germany amid the global refugee crisis. The research delves into language barriers, discriminatory encounters, administrative hurdles, and professional development complexities within the broader context of the war-induced displacement of individuals with a third-state status. Qualitative data were collected through semi-structured, in-depth interviews with five African refugees aged 23–27 in Germany. Analysing the data through qualitative content analysis, four main categories emerged: integration challenges, physical and mental health, quality of life, and factors influencing well-being. The findings highlight multifaceted integration challenges, encompassing language barriers, discrimination, administrative complexities, and professional development difficulties. Participants reported stress from simultaneous language learning and employment, social isolation, and fear of returning home. Although physical health was generally rated as good, mental health challenges arose, linked to the dual burden of integration and professional advancement. Unsatisfactory quality of life stemmed from unmet basic needs, including employment, housing, and travel to visit family. Despite significant challenges, participants displayed resilience and optimism. The study emphasises the need for targeted interventions and support systems tailored to the unique struggles of African refugees from the Ukrainian war in Germany. Policymakers, refugee-support organisations, and community-based groups can use these findings to develop programs enhancing integration and well-being for this population.